The 7 habits of highly effective people : powerful lessons in personal change - Covey, Stephen R., 1932-2012; Collins, Jim, ....- (London : Simon & Schuster, 2013)
25 years, 20 million copies sold! This 25th anniversary edition of Stephen Covey's beloved classic commemorates the timeless wisdom of the 7 Habits.
Keywords: business ; success